Influencing early childhood education key figures, philosophies and ideas - Pound, Linda (Maidenhead, Berkshire, England McGraw Hill/Open University Press, 2011)
"'Thinking about [i.e. "Influencing"] early childhood education' will offer an academic and critical approach to the wealth of theories that underpin elements of current practice in early childhood care and education. It will focus on analyzing the rise and interconnectedness of theories of learning and development. It will range from key nineteenth century movements to progressive ideas of the twentieth century, encompassing psychoanalytic theories, deconstructing theories and constructivism and behaviourism."--Publisher's website.
Thinking about early childhood in the nineteenth century. Robert Owen, 1771-1858 -- Friedrich Froebel, 1782-1852 -- Progressive ideas of the twentieth century. Margaret McMillan, 1860-1931 -- Rudolf Steiner, 1861-1925 -- Maria Montessori, 1870-1952 -- Susan Isaacs, 1885-1948 -- Psychodynamic theories and their impact. Sigmund Freud (1856-1939) and the development of psychoanalytical theories -- Psychodynamics and young children -- John Bowlby (1907-1990) and attachment theories -- Emotion and cognition -- Constructivism and behaviourism. Burrhus Skinner (1904-1990), behaviourist theories and approaches -- Jean Piaget (1896-1980) and constructivism -- Lev Vygotsky (1896-1934) and social constructivism -- Challenging theories and practice in the twentieth century. De(constructing) schooling -- Deconstructing early childhood -- Deconstructing development -- Weighing up the evidence. Final thoughts.
Keywords: Early childhood education; Early childhood education -- Philosophy